(untitled) (Al-Qamar, 2022)
Imām Fakhr ad-Dīn ar-Rāzī, often known by the sobriquet Sultan of the theologians, was a Persian polymath, Islamic scholar and a pioneer of inductive logic-, and his extremely wide-ranging exegesis of the holy Qur’an (Mafāṭīḥ al-Ġhayb) which ranks among the greatest works of its kind in Islam. In his Tafsir, any interpolations introduced by the erring sects in interpretation of the holy Quran has been discussed in full and then refuted with detailed arguments. And hence, a huge amount of criticism is found against Mu’tazila in his tafsir. This article is an attempt to discuss the influence of Mu’tazila on contemporary exegetes, and to refute such deviated ideas on the name of modernism, demonstrating Imam Razi’s rectifications of Abdul Jabbar al Mutazili’s views in his Commentary known as “Mafāṭīḥ al-Ghayb’’